Potato early blight epidemics and comparison of methods to determine its initial symptoms in a potato field (2007)
The influence of an early blight epidemic on potato tuber yield was evaluated in three field experiments during 2000 to 2002 crop seasons under Viçosa, Minas Gerais state growing conditions. Through a disease severity gradient method, used four different dosages of fungicide chloratalonil were obtained four epidemic levels with severity range of D1 (maximum), plot without fungicide treatment, to D4 (minimum), plot with fully dosage fungicide commercial recommended, were obtained, which allowed for comparison of the epidemic effect on plant growth and tuber yield, and indicated the time for initiating of the first early blight (Alternaria solani) lesions on potato foliage The disease was predicted by using the methods based either degree days (DD) with base temperature of 7oC and physiological days (PD) having minimum, optimum and maximum temperature of 7, 21 and 30oC, respectively, accumulated during the period between planting and the first symptom appearance. Plots with higher disease levels along the gradient had significantly loss tuber yield in all trials. The highest yield reduction of 49,6; 52,7 and 58,2% occurred in D1, plots without fungicide treatment, during the years 2000, 2001 and 2002, respectively. The epidemic prediction through accumulated DD or PD did not indicate the appropriate time to initiate the epidemic control. However, the PD method that predicted the first symptoms between 240 and 333 accumulated PDs was found to be more adequate. The data revealed that green leaf area and tuber yield reduction caused by the early blight is dependent upon the disease severity. Compared to the others, the PD method appears to be most suitable to determine when the disease will establish, and thus can be recommended to initiate the disease management at 250 accumulated PDs, under disease-favorable climatic conditions.